Is There Room for Foreign Exchange Interventions Under an Inflation Targeting Framework? Evidence from Mexico and Turkey - Domaç, Ilker (World Bank, Washington, D.C., 2013)
The salient characteristics of emerging market economies coupled with the increasing adoption of inflation targeting in these countries has stimulated much debate about the role of the exchange rate in inflation targeting regimes. The authors aim at shedding more light on this issue by investigating whether central bank foreign exchange interventions have had any impact on the volatility of the exchange rate in Mexico and Turkey since the adoption of the floating regime. To this end, their study, using daily data on foreign exchange intervention, employs an Exponential GARCH framework. Empirical results suggest that both the amount and frequency of foreign exchange interventions have decreased the volatility of the exchange rates in these countries. The authors' findings corroborate the notion that if foreign exchange interventions are carried out with finesse and sensibly-that is, not to defend a particular exchange rate-they could play a useful role in containing the adverse effects of temporary exchange rate shocks on inflation and financial stability.